Guntur galunggung song: text and symbolic meaning review - Saiful, Abizar Algifari; Sukmayadi, Yudi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
Mang Koko's 'Guntur Galunggung' is one of the most evocative and innovative songs in Sundanese music, created in response to the 1982 eruption of Mount Galunggung. This song represents a collaborative effort between Sundanese writer Wahyu Wibisana and musical artist Mang Koko, showcasing uniqueness in its thematic background, musical arrangement, and lyrical meaning. The research employs descriptive analysis, focusing on data processing through content analysis of music manuscripts. Data collection methods include observation, interviews, and literature studies. This analysis provides an in-depth review of the innovative Sundanese musical work, 'Guntur Galunggung,' highlighting its musical complexity and interrelated symbolic meanings. The research results reveal the intricate structure of the song "Guntur Galunggung," comprising 12 stanzas of rumpaka, 12 stanzas of gending accompaniment, and distinct sections with varying musical elements, while symbolically depicting the life of a local couple, Mang Maman, and Bi Warsih, emphasizing themes of simplicity, gratitude, resilience, and adaptation in the face of challenges, culminating in their migration to Sumatra as a metaphorical journey of rising after a fall.